Digitalization: Definition and measurement - Guyllaume Faucher; Stephanie Houle (Bank of Canada, 2023)
How has digitalization shaped the landscape of Canada's economy? In this paper, we seek to grasp the breadthof digitalization. We define digitalization and distinguish it from other related concepts, such as information and communication technologies (ICT) and the digital economy. We then assess the scope of digitalization in Canada by looking at measures based on outputs and inputs as well as the challenges that come with trying to estimate it. Finally, we raise important questions for future research about the impacts of digitalization.
Keywords: E; E0; E01; O; O3; O33; O5; O51; 330; Digitalization; Potential output